Work and object explorations in the metaphysics of art - Lamarque, Peter (Oxford : Oxford University Press, 2010)
Exploring certain fundamental metaphysical aspects of works of art, this book gives focus to a distinction between works and the materials that underlie or constitute them. This constitutive material might be physical or abstract.
Description based on online resource; title from PDF title page (viewed on Sept. 7, 2010).
Includes bibliographical references and index.
Keywords: Arts -- Philosophy; Aesthetics